2009
DOI: 10.1515/jpm.2009.001
|View full text |Cite
|
Sign up to set email alerts
|

Is induced abortion a risk factor in subsequent pregnancy?

Abstract: Objective: To determine whether a history of terminations of pregnancy influences subsequent pregnancies in terms of pregnancy risks, prematurity and neonatal biometrics. Patients and methods:Based on the perinatal statistics of eight German federal states, data of 247,593 primiparous women with singleton pregnancies born between 1998 and 2000 were analyzed. The control group consisted of primiparous women without previous induced abortions. Maternal age was adjusted for. Results: There was an overall trend to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 17 publications
3
7
1
1
Order By: Relevance
“…In keeping line with earlier studies, we found the demographic characteristics of the first‐time mothers who had previous induced TOP different from those first‐time mothers having no history of induced TOP. As in previous studies, during the time period where most of the induced TOPs were surgical, our study found an increased risk for extremely preterm birth among the women with at least two surgical induced TOPs compared to the women with no history of induced TOP. In contrast to some previous studies, we did not find any significant increased risk for preterm birth after one surgical or medical induced TOP; however, this is similar to the finding of a previous study from Finland .…”
Section: Commentsupporting
confidence: 87%
“…In keeping line with earlier studies, we found the demographic characteristics of the first‐time mothers who had previous induced TOP different from those first‐time mothers having no history of induced TOP. As in previous studies, during the time period where most of the induced TOPs were surgical, our study found an increased risk for extremely preterm birth among the women with at least two surgical induced TOPs compared to the women with no history of induced TOP. In contrast to some previous studies, we did not find any significant increased risk for preterm birth after one surgical or medical induced TOP; however, this is similar to the finding of a previous study from Finland .…”
Section: Commentsupporting
confidence: 87%
“…10 Moreover, the results of our study are consistent with the findings of others reporting an increased risk of adverse outcomes in women with a prior IAB. 4,10,[21][22][23][24] Chen et al found lower odds for preterm delivery in women with one mifepristone abortion compared with women with no abortion. 25 Reasons for the association between both SAB and IAB and subsequent PTB are unclear.…”
Section: Commentmentioning
confidence: 99%
“…Although findings on the association between prior pregnancy termination and subsequent preterm delivery have been mixed (Pickering and Forbes, 1985; Henriet and Kaminski, 2001; Moreau et al ., 2005; Raatikainen et al ., 2006; Virk et al ., 2007; Brown et al ., 2008; Voigt et al ., 2008, 2009; Freak-Poli et al ., 2009), the observed ‘dose–response relationship’ between number of pregnancy terminations and preterm risk, as demonstrated in a recent meta-analysis by Shah and Zao (2009) provides strong evidence in favor of an association between pregnancy termination and preterm birth. The strong association between prior pregnancy termination and cervical insufficiency irrespective of race/ethnicity was confirmed in our analysis.…”
Section: Discussionmentioning
confidence: 99%